Persepsi Konsumen terhadap Fasilitas Makanan dan Minuman serta Operasional Hotel Syariah di Jabodetabek (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Halal tourism has continued to grow as a highly attractive segment for Muslim travelers, particularly in the provision of Sharia-compliant accommodation such as Islamic hotels. This study aims to examine consumer perceptions of halal food-and-beverage facilities and Sharia-based operational standards in Islamic hotels across the Greater Jakarta area (Jabodetabek). A descriptive quantitative approach was employed, involving 150 respondents who had stayed in Sharia hotels. Data were collected through closed-ended Likert-scale questionnaires and analyzed using the Weighted Mean Score (WMS) technique to evaluate respondents’ assessments of each indicator. The results indicate that consumer perception of halal food-and-beverage facilities falls into the very high category, with average scores exceeding 4.838. Consumers acknowledged that Sharia hotels maintain halal assurance, hygiene, and food safety through proper processing and the availability of halal certification. Regarding operational aspects, consumer perception is also classified as very good, with an average score of 4.606, particularly for policies prohibiting unmarried couples from sharing a room and banning entertainment deemed inappropriate or immoral. However, the use of Sharia-compliant financial institutions still requires improvement. Overall, the findings affirm that Sharia hotels in Jabodetabek have successfully implemented most Sharia principles, although further enhancement of internal operational practices is needed to achieve more comprehensive Sharia compliance.